2019
DOI: 10.1080/03088839.2019.1693065
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting urban hierarchy and specialization from a maritime perspective

Abstract: Port-city relationships have attracted paramount attention from a variety of scientific disciplines for several decades, such as geography, history, planning, regional science, sociology, and economics to name but a few. Yet, the extent to which maritime traffic specialization obeys the same spatial distribution than other economic activities remains underexplored today. This article tackles this lacunae head on by proposing an empirical analysis of the way vessel tonnage per main categories of flows (e.g. con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…At the European level, Ducruet et al (2010) found a significant correlation between commodity diversity and traffic size, albeit many exceptions. Numerous small and medium-sized ports situated at the periphery and/or on islands could reach a comparable traffic diversity than Rotterdam and other large mainland gateways, thanks to their captive hinterland, protected from competition (see also Ducruet, 2020 for a global perspective).…”
Section: Introductionmentioning
confidence: 99%
“…At the European level, Ducruet et al (2010) found a significant correlation between commodity diversity and traffic size, albeit many exceptions. Numerous small and medium-sized ports situated at the periphery and/or on islands could reach a comparable traffic diversity than Rotterdam and other large mainland gateways, thanks to their captive hinterland, protected from competition (see also Ducruet, 2020 for a global perspective).…”
Section: Introductionmentioning
confidence: 99%
“…), and in a comparative manner, to check whether larger cities handle more diversified traffic (cf. Ducruet, 2020a; Ducruet et al, 2010), and whether larger traffic occurs in more diversified economies.…”
Section: The Complexity Of Port‐city Relationshipsmentioning
confidence: 99%
“…According to Pumain (2006) and Pumain et al (2009), the "largest cities became larger because they were successful in adopting many successive innovations [while] the most advanced technologies concentrate in largest cities". In terms of maritime flows and networks, there is a path-and place-dependent process by which the most populated cities are the most diversified in terms of traffic type Ducruet 2020).…”
Section: Introductionmentioning
confidence: 99%